THE EFFECTIVENESS OF INTERACTIVE MULTIMEDIA BASED ON AUGMENTED REALITY IN GEOGRAPHY LESSONS TO IMPROVE LEARNING OUTCOMES - Lusty Firmantika; Bella Izzatun Nafsi (SOSIOEDUKASI, 2025)
This study aimed to examine whether interactive multimedia based on Augmented Reality (AR) can improve students’ learning outcomes in the Natural Disaster Mitigation topic at MA Ahmad Yani Jabung. The research employed a quantitative approach with a one-group pretest–posttest design involving 16 Grade XI students selected through purposive sampling. A 12-item multiple-choice test was used to measure learning outcomes and was validated through expert judgment, Pearson’s correlation, and reliability testing, yielding Cronbach’s Alpha coefficients of 0.874 (pretest) and 0.904 (posttest). Data were analyzed using a paired t-test and N-Gain score. The results revealed a notable improvement, with average scores increasing from 55.21 (pretest) to 82.81 (posttest), categorized as moderate to high improvement based on the N-Gain value. The paired t-test indicated a statistically significant difference in students’ scores before and after the intervention (p < 0.05). These findings demonstrate that AR-based interactive multimedia is effective in enhancing geography learning outcomes by providing engaging, interactive, and contextually meaningful learning experiences.